French-english bilingualism as a determinant of learners general language competence in some selected secondary schools in Ibadan (2017)
The poor performance in English and French language in public examinations has called for concern among stakeholders in the field of language education in Nigeria. While students recorded low performance in English across the years, there is low turn- out of students in French language. Researchers have looked into the viability of bilingualism in English and French as a symbiotic measure to finding lasting solution to the problem of general language deficiency among Nigerian learners’ of English and French language respectively. Therefore, this study sought to investigate the complimentary role of English and French language in the attainment of general language competence of some bilingual students in Ibadan, Oyo state. Purposive sampling technique was used to select 156 students in four junior secondary schools in Ibadan. Three research questions were raised. Two instruments were used to collect data i.e. English language achievement test (ELAT) and French language achievement test (FLAT). The result shows that there was significant difference in the bilingualism in French and English language among the selected students in the secondary school in Ibadan (t = 7.922, df = 155, P<0.05). There was no Gender difference in the attainment of Bilingualism in English and French from the selected secondary schools. (t-cal=-279 lesser than t-crit-1.95, P>0.05) There are significant relationships between students’ performance in English and French Language (r- 0.363, P<.05). It is therefore recommended that French and English should be taught concurrently to the students as their performance in French will aid their performance in English language The study examined the influence of anxiety on the success of some pre-service teachers of French Language in selected tertiary institutions in southwestern Nigeria. Descriptive research design was adopted. A total of 130 preservice teachers (male — 40 and female — 90) participated in the study. The results showed that the test anxiety level of pre-service teachers' foreign language anxiety is slightly low (X = 2.32, Std. Dev = 1.162). The findings further showed that the fear of negative evaluation level of pre-service teachers' foreign language anxiety is a bit high (X = 2.65, Std. Dev = 1.227). Data collected were analysed using PPMC and Regression Analysis. The results showed that the communication apprehension level of pre-service teachers' foreign language anxiety was slightly low (X = 2.29, Std. Dev — 1.188). There was no influence of age on pre-service teachers’ foreign language anxiety in classroom (F value —1.349, P>0.05). There was no gender difference in the pre-service teachers’ foreign language anxiety in classroom (t-Critical value (t-Crit—1.99, P>0.05). Length of years of French study had no influence on the pre-service teachers’ foreign language anxiety in classroom (F value — 1.349, Pro— 0.262>0.05). It was however recommended that pre-service teachers of French language in tertiary institutions should pay maximum attention to the variants of foreign language anxiety of fear of negative evaluation, communication apprehension and test anxiety in the process of learning French language as a foreign language.